Breast cancer with scalp metastases: a case report - Ahmad M. Abdulraheem; Duha Naji; Ammar N. Al Heyasat; Mohammad Alhasan; Nidal M. Almasri; Raghad Odeh (Journal of Medical Case Reports, 2023)
Abstract Background While breast cancer is the most common cancer in women, cutaneous metastases are rare in breast cancer. Additionally, scalp involvement in breast cancer metastasis is extremely rare. That being said, scalp lesions should always be thoroughly investigated to distinguish metastatic lesions from other neoplasms. Case presentation A 47-year-old female Middle-Eastern patient presented with metastatic breast cancer in the lungs, bone, liver, and brain with no signs of multiple organ failure, in addition to cutaneous metastases, including the scalp. Between 2017 and 2022, she was managed through modified radical mastectomy, radiotherapy, and several lines of chemotherapy. She presented in September of 2022 with enlarging scalp nodules, which started developing 2 months prior to her presentation. Physical examination revealed firm, non-tender, and immobile skin lesions. Magnetic resonance imaging scan of the head showed soft tissue nodules in different sequences. A punch biopsy was taken from the largest scalp lesion and showed metastatic invasive ductal carcinoma. A panel of immunohistochemistry stains was applied, because a single specific marker for differentiating primary cutaneous adnexal tumors or other malignant neoplasms from breast cancer has not yet been identified. The panel showed positive estrogen receptor 95%, progesterone receptor 5%, negative human epidermal growth factor receptor 2, positive GATA binding protein 3, positive cytokeratin-7, negative P63, and negative KIT (CD117). Conclusion Breast cancer metastases to the scalp are extremely uncommon. When a scalp metastasis is present, it might be the only symptomatic sign of disease progression or widespread metastatic lesions. However, such lesions warrant a comprehensive radiologic and pathologic workup to rule out other possibilities of skin pathologies, such as sebaceous skin adenocarcinoma as it effects the management plan.